P4-S1.01 Role of Chlamydia trachomatis heat shock proteins 60 and 10 in induction of apoptosis in endocervical epithelial cells. (10th July 2011) - Mittal, A S N; Jha, R; Salhan, S
Abstract : Background: Chlamydiae are known to modulate host cell to escape from immune response and prolong their persistence to cause fallopian tube damage, ectopic pregnancy and infertility. In addition, Chlamydiae have been reported to elicit both the induction of host cell death, or apoptosis, under some circumstances and actively inhibit apoptosis under others. Chlamydial heat shock proteins (cHSPs) have been known to be responsible for proinflammatory pathologic manifestations of human chlamydial disease in the reproductive tract. Moreover, cHSP60 has been shown to induce apoptosis, in vitro, in primary human trophoblasts, placental fibroblasts, and the JEG3 trophoblast cell line. However, no study has been dedicated to their potential role in apoptosis of primary cervical epithelial cells that are privilege target for chlamydial infection. In the present study, we investigated the ability of cHSP60 and cHSP10 to induce apoptosis in primary cervical epithelial cells. Methods: Primary cervical epithelial cells were stimulated with cHSP60 and cHSP10 for 4 h. Quantitative measurements of apoptosis have been performed by cytofluorometry and apoptosis-related genes were analysed by microarray, real-time PCR and western blotting. Further, levels ofd proinflammatory cytokines (IL-18 and IL-1ß) were determined by semi-quantitative RT-PCR. Results: Treatment with cHSP60 significantly increased the mean percentage of apoptotic cells (57.4±5.9 % vs 9.3±1.2 % in control cells, p <0.05). Similarly, treatment with cHSP10 significantly increased the mean percentage of apoptotic cells (47.8±4.8 % vs 9.3±1.2 % in control cells, p <0.05). A cDNA microarray study showed significant (p <0.05) upregulation of interleukin (IL)-1 ß-convertase, caspase-3, -8 and -9 genes were confirmed in real-time RT-PCR in cHSP60 and cHSP10 stimulated than in control cells. The transcript levels of IL-1ß and IL-18 in cells treated with cHSP60 and cHSP10 was found to be significantly (p <0.05) higher in stimulated than in control cells. Conclusions: In women with persistent chlamydial infection, the release of extracellular cHSPs may lead to cell apoptosis and to an inflammatory response involved in fibrosis and scarring of female genital tract that may contribute severe tubal pathologies including infertility.